Identification and characterisation of myofibroblast markers in human colon and colorectal cancer microenvironment - Hsia, L; Bodmer, W (2015)
Myofibroblasts (MFs) are one of the most significant stromal cell types in epithelia such as in the gut. They play an important role in regulating the normal colorectal stem cell niche and facilitating tumour initiation, growth and progression through inter-cell signalling. Abundant presence of MFs is often associated with poor prognosis in cancers. The aim of this project is to identify new myofibroblast markers to distinguish them from others cells in the stroma, and also to establish patterns of myofibroblast gene regulation. First, we identify the membrane protein that home-raised IgG1 antibody PR2D3 recognises on myofibroblasts, by using immunoprecipitation and mass spectrometry based amino acid sequencing, as the AOC3 membrane primary amine oxidase, with additional reactivity to myosin heavy chain 11 (Chapter 3). The AOC3 expression in myofibroblasts in vivo and in vitro is validated by extensive expression profiling analyses. Our results demonstrate that AOC3 is expressed by myofibroblasts and that it functions as an SSAO enzyme (Chapter 4). Furthermore, we successfully separated primary myofibroblasts from fresh tissues by FACS sorting using AOC3 as a myofibroblast-specific surface marker (Chapter 5). Analysis of whole genome microarray mRNA expression profiles between myofibroblasts and fibroblasts revealed 4 candidate genes that were the most significantly differentially expressed in the two cell types; NKX2.3 and LRRC17 are highly expressed in myofibroblasts, while SHOX2 and TBX5 are highly expressed in fibroblasts (Chapter 6). NKX2.3 is essential for TGFβ-induced myofibroblast contraction and migration ability. Knockdown of NKX2.3 using siRNA caused a decrease of myofibroblast-related gene (ACTA2, MYH11 and AOC3) expression and an increased expression of fibroblast gene, SHOX2 in myofibroblasts. This suggests that NKX2.3 is a key mediator for maintaining myofibroblast characteristics and functions. Our work presented here shows that myofibroblasts and fibroblasts have significantly different expression profiles for a few key genes and that they differ in their response to TGFβ. In conclusion, the results clearly show that TGFβ activated fibroblasts and myofibroblasts, as defined by the expression of AOC3 and NKX2.3, are distinctly different cell types.